Measurement and compensation of spillover effect in underwater acoustic sensor networks during target localization. (May 2023) - Reddy, Tippireddy Srinivasa; Prateek,; Arya, Rajeev
Localization in underwater acoustic sensor networks (UWASNs) depends critically on the mobility pattern of the topology as well as the target node. Prior literature has attempted to localize static as well as dynamic sensors. However, unintentional movement of the sensor network introduces localization errors which add up cumulatively and disrupt the normal functioning of an underwater sensor network. In the present work, the concept of spillover has been defined to denote these unintentional movements. The genesis of spillover has been discussed with respect to the signal model. A theorem is proposed to describe the consequence of spillover on the UWASN. The problem of spillover is quantified mathematically. The loss of localization performance due to the spillover effect is then measured with the formulation of a control function which incorporates delay time. To mitigate the losses, a spillover compensation (SoC) algorithm is proposed. SoC utilizes a discretization technique to reduce the variance of sensor position and to enhance localization accuracy. It improves the performance of localization by at least 23.15% and reduces the localization error by 31% up to 600 m. Through a series of computations using parameters such as root mean square (RMS) positioning error and RMS velocity error, the theoretical findings are verified and compared with standard techniques. Diversity in deployment scenarios is taken care of using variance and sensor speed. The proposed technique shall be useful to create spillover-aware systems in underwater cybernetic localization and UWASNs in general.